Impresiones de España recogidas por un alemán entre la Ilustración y el Romanticismo: Christian August Fischer y sus libros de viaje - Raders, Margit (Revista de Filología Románica, 2006)
The writer Christian August Fischer (1771-1829) can be considered the most important and influential disseminator of Spain and Spanish culture in the German speaking countries at the turn of the 19th century. In fact, until the mid 19th century, his travel books about Spain were among the most read within a genre that, in itself, enjoyed great popularity. In this paper, we offer a selection of meaningful passages taken from those books in order to analyse how Fischer perceived the Spanish reality and transmitted it to the German readers. We will pay particular attention not only to his descriptions relating to the physical environment, but also to his approach to the country’s inhabitants –the Spanish society of the time–, both in his perception of the rural atmosphere and his description of the capital’s urban life. Based on the motto «men have national characters, women national moods», his particular vision of a different reality to his own also includes an evaluation of the national psychology of Spanish men and women.